Preliminary measurements of transient boundary heat transfer process under supercritical pressures using pixelated phase-shifting interferometry. (November 2022) - Zhang, Yizhi; Chen, Lin; Wu, Qixian; Yang, Dong; Kanda, Yuki; Zang, Jinguang; Komiya, Atsuki; Huang, Yanping
Abstract: The boundary heat transfer dynamics of supercritical carbon dioxide (CO2 ) is vital to its application in solar heater, extraction, refrigeration, heat pumps, power generations, nuclear systems and many other occasions. In this study, an experiment system using pixelated-array masked phase-shifting interferometer has been established for the visualization of temperature of supercritical CO2 . The laser diagnostic process has been operated with a carefully designed visualization chamber to give clear transient results of the density and temperature fields for the first time. Those field information has been used to calculate the heat transfer characteristic parameters of the supercritical CO2 fluid in different boundary conditions. The current quantitative visualization analysis by the utilization of pixelated methods is shown capable of giving transient analysis of detailed field evolutions. The results show that (1) small temperature differences are generated in supercritical boundary due to the typical large thermal capacity; (2) supercritical convection boundary is with much quicker thermal quenching than subcritical states, while the subcritical states boundary parameter show localized characteristics while supercritical cases show fluctuation phenomena; (3) the boundary fluctuations heat transfer field exist for supercritical states and the fluctuations affect the overall heat transfer behaviour and the field evolution in supercritical states.